KEPUASAN PELANGGAN PADA USAHA JASA PENDIDIKAN DAN PELATIHAN LUAR RUANG - Didik Daryanto (Fakultas Ekonomi Universitas 45 Surabaya, 2015)
Customer satisfaction is very important to a company's services, because satisfied customers will come back, buy more, spread the experience to another friend, and is willing to pay more to do business with a trusted provider. Efforts to maintain customer satisfaction one of which is to monitor what they want from the services that are presented. This study aimed to measure the level of customer satisfaction in the business of outdoor education and training, in which customer satisfaction is measured on the dimensions of perceived service and expected service. The population in this study is service users of the outdoor education and training at the Centre for Education and Training Managerial Behavior University of Wijaya Putra that training in January and June 2014, samples were taken by purposive random sampling technique amounts to 143 people. The variables of this study customer loyalty, service quality, perceived quality, perceived value, and customer expectation and customer complaints. Analysis of the data used is multiple linear regression analysis with hypothesis testing with the F test and t test. The expected outcome of this research is the acquisition of the factors that affect customer satisfaction on service providers of outdoor education and training, in terms of quality of service indicators (tangibles, reliability, responsiveness, assurance and empathy). The results show that there is good agreement between the performance perceived by the user's expectations of the outdoor education and training services. These conditions can be considered satisfactory by management for the success of providing the best service to users of the service. Cartesian diagram determine the right strategy for the management to improve service quality are a top priority especially.